2018
DOI: 10.7150/ijms.22793
|View full text |Cite
|
Sign up to set email alerts
|

Viola Yedoensis Suppresses Cell Invasion by Targeting the Protease and NF-κB Activities in A549 and Lewis Lung Carcinoma Cells

Abstract: Cancer metastasis is a vital trait in malignancies with complicated early diagnosis and therapeutic management. Therefore, the development of new remedies and the utilization of natural medicines that target metastasis are of great interest and have been studied extensively. Chinese medicinal herbs have various anti-carcinogenesis properties; however, the in vitro effect and mechanism of Viola yedoensis on cancer cell metastasis remains poorly understood. V. yedoensis extracts (VYE) can suppress the invasion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Huang et al suggested that Viola Yedoensis extract (VYE) regulated MMP-2 and uPA expression via the down-regulation of NF-κB pathway. Due to this process, VYE potentially suppressed the invasion, migration, and proteinase activities of A549 and Lewis lung carcinoma (LLC) cells, which consequently contributed to the inhibition of lung cancer cell metastasis [ 49 ]. Fan et al confirmed the capability of BushenShugan Formula (BSF) to inhibit proliferation, invasion, and cancer stem cell (CSC) properties of A549 cells, decrease colony formation, and induce cell apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al suggested that Viola Yedoensis extract (VYE) regulated MMP-2 and uPA expression via the down-regulation of NF-κB pathway. Due to this process, VYE potentially suppressed the invasion, migration, and proteinase activities of A549 and Lewis lung carcinoma (LLC) cells, which consequently contributed to the inhibition of lung cancer cell metastasis [ 49 ]. Fan et al confirmed the capability of BushenShugan Formula (BSF) to inhibit proliferation, invasion, and cancer stem cell (CSC) properties of A549 cells, decrease colony formation, and induce cell apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, under the targeting effect of exosomes and the effect of EPR, drugs can better target the tumor site and exert a therapeutic effect. From the H&E staining of major organs, it could be found that there were slight voids appearing in the cytoplasm of the liver, lung and kidney in each administration group, especially in the lung, this may be related to the high metastasis of A549 tumor cells (Huang et al, 2018 ), while from the H&E staining of tumor, the Cy5.5-EXO-DTX presented better antitumor efficacy in A549 tumor-bearing mice models than Cy5.5-DTX group. This may be due to the targeting of drugs after the inclusion of exosomes, which can guide the specific delivery of drugs to tumor tissues, improve the efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Further research showed that VYE inhibits the binding of NF-κB to DNA. Thus, the inhibition of NF-κB suppresses MMP-2 and u-PA expression and lung cancer cell invasion [ 46 ]. Focal adhesion kinase (FAK) was found to be overexpressed and activated in some late-stage cancers.…”
Section: Effects Of Natural Products On the Tumor Microenvironmentmentioning
confidence: 99%